THE DEVELOPMENT OF CONFLICT THROUGH PLOT IN EDGAR ALLAN POE’S THE TELL-TALE HEART - Kezia Meily Nicharisa S; Aprilia Anzani; Eunike Anastasya Manurung; Nurhayati Purba (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study analyzes the development of conflict through plot structure in The Tell-Tale Heart by Edgar Allan Poe. The research aims to identify the types of conflict presented in the story and explain how the plot contributes to the progression of these conflicts. This study employs a qualitative descriptive method using the short story as the primary data source. The analysis is based on Freytag’s Pyramid Theory to examine plot stages such as exposition, rising action, climax, falling action, and resolution, and Stanton’s Conflict Theory to classify conflicts into internal and external types. The findings reveal that internal psychological conflict dominates the narrative, reflected in the narrator’s obsession, fear, guilt, and paranoia, while external conflict appears between the narrator, the old man, and the police. The plot structure gradually intensifies these conflicts at each stage, culminating in the narrator’s confession and psychological collapse. The interaction between plot and conflict strengthens narrative tension and reinforces the theme of madness. Therefore, plot and conflict function interdependently in shaping the psychological and structural development of the story.